Editorial Perspective: Speaking up for developmental language disorder – the top 10 priorities for research. (1st April 2022) - Kulkarni, Amit A.; Chadd, Katie E.; Lambert, Sarah B.; Earl, Gill; Longhurst, Lauren M.; McKean, Cristina; Hulme, Charles; McGregor, Karla K.; Cunniff, Anna; Pagnamenta, Emma; Joffe, Victoria; Ebbels, Susan E.; et al.
Abstract : Developmental language disorder (DLD) is one of the most common neurodevelopmental conditions, yet is chronically underserved, with far fewer children receiving clinical services than expected from prevalence estimates, and very little research attention relative to other neurodevelopmental conditions of similar prevalence and severity. This editorial describes a research priority‐setting exercise undertaken by the Royal College of Speech and Language Therapists, which aims to redress this imbalance. From consultations with researchers, practitioners and individuals with lived experience, 10 research priorities emerge. Our goal is to share these priorities with the wider research community, to raise awareness and encourage research collaboration to improve outcomes for young people with DLD.